The Role of Taxpayer Trust and Awareness on Voluntary Compliance: An Experimental Study - I Putu Hendra Martadinata; I Nyoman Putra Yasa (Universitas Pendidikan Ganesha, 2022)
This study is a development of previous research which found that fair treatment from the tax authorities were not able to encourage taxpayer compliance. It is suspected that this is caused by another personality element, namely taxpayer awareness. Therefore, this study examines the effect of taxpayer trust and awareness on taxpayer voluntary compliance using the experimental method. The participants of the experiment were 106 students of Undergraduate Accounting Program, Ganesha University of Education. The results of this study found that trust in tax authorities is a very important factor in shaping compliance behavior, especially for taxpayers who have low tax awareness. Meanwhile, taxpayer awareness has an important role in shaping compliance behavior when the condition of trust in tax authorities is low. The results of this study are expected to contribute theoretically and practically, to emphasize the importance of forming taxpayer awareness and trust in tax authorities.